Perfil sociodemográfico e uroginecológico de mulheres com incontinência urinária atendidas no serviço de fisioterapia na Amazônia - COSTA, Brunna Gabrielli Freitas da (2022)
Objective: To know the sociodemographic and urogynecological profile of women with urinary incontinence attended at a public service in the Amazon. Methodology: It was a cross sectional, documentary, and quantitative study. The sample consisted of women with urinary incontinence who were assisted by the physiotherapy service in the period of 2017-2020. The personal data, gynecological history, sexual history and urological symptoms were collected and the physical examination was performed using the PERFECT protocol. Results: The study consisted of 51 medical records, with an average age of 52.7±10.7 years old, 49% of the women were married, 46.9% were housewife, 89.4% of them lived in Belém, 88.2% had income up to one minimum wage, 41.1% had completed high school and they presented as gynecological antecedents, that 62.7% were postmenopausal women, 84.3% did not undergo hormone replacement therapy, 50% had normal labor and 68.62% had active sexual life. Concerning the types of urinary incontinence, 54% had IUM, 34% SUI and 12% UUI. Regarding the PERFECT protocol, the average muscle performance (P) was 2.1. Conclusion: Adult, postmenopausal, multiparous women have mixed urinary incontinence and pelvic floor muscle contraction graded as weak Therefore, Knowing thos profile we can contribute that assertive preventive and treatment public policies can be designed.